SIMULATION OF THE PROPERTIES OF A357 ALUMINUM ALLOY IN SEMI-SOLID STATE FOR EXTRUSION ADDITIVE MANUFACTURING OF METAL (ASEAN Engineering Journal, 2025)
In general, the primary issues related to the present design are primarily the high temperature range, which is generating enormous thermal loads to the machinery, and the inability of achieving even temperature distribution in the workpiece. The new approach in this paper mitigates these issues for the aluminum alloy extrusion process using a screw extruder equipped with a Double Wave Screw (DWS). The extrusion screw is typically divided into three regions: the feeding region, the compression region, and the metering region. The DWS component is designed for the compression and metering regions to achieve maximum shear rate in extrusion, to create globular microstructure. Furthermore, our work aims to predict significant process parameters such as viscosity, shear rate, and material flow velocity to determine the feasibility of 3D printing. In order to validate the effectiveness of the material extrusion process in the 3D printing process, the model has been simulated through the finite element method (FEM) by employing the power-law model, which describes the non-Newtonian behavior of the composite semi-liquid aluminum needle. Simulation has demonstrated that control of the material outlet temperature can generate a semi-liquid state of aluminum. Besides, the DWS configuration enhances the shear rate and homogeneity of the molten metal, ultimately leading to enhanced mechanical properties of the product extruded.